High expression of programmed cell death 1 ligand 1 in lung adenocarcinoma is a poor prognostic factor particularly in smokers and wild‐type epidermal growth‐factor receptor cases. Issue 1 (15th December 2016) - Mori, Shohei; Motoi, Noriko; Ninomiya, Hironori; Matsuura, Yosuke; Nakao, Masayuki; Mun, Mingyon; Okumura, Sakae; Nishio, Makoto; Morikawa, Toshiaki; Ishikawa, Yuichi
Abstract : A clinical implication of programmed cell death 1 ligand 1 (PD‐L1) expression in lung adenocarcinoma has not been well established. We evaluated PD‐L1 expression immunohistochemically on 296 surgically resected lung adenocarcinomas to investigate a clinical implication of PD‐L1 expression especially in terms of smoking history and epidermal growth‐factor receptor (EGFR) mutation status. Patients were classified into high‐ and low‐PD‐L1 expression groups. The high‐expression group ( n  = 107) showed a significantly higher proportion of smokers and poor differentiation compared with the low‐expression group ( n  = 189). Survival analysis showed that the prognosis of the high‐expression group was worse in overall survival than that of the low‐expression group (3‐year overall survival 85 vs. 94%, P  = 0.005). Stratified survival analyses showed that the prognoses of the high‐expression group were worse than those of the low‐expression group in both strata of smokers and wild‐type EGFR ( P  = 0.009 and P  = 0.007, respectively). We found that high PD‐L1 expression was a poor prognostic factor in the smokers or the patients with wild‐type EGFR, whereas it was not the case in those who never smoked or those with EGFR mutation, implying the importance of adenocarcinoma driver mutations and etiology.